Negotiating the complexities of English language teaching in a religiously rooted environment: Indonesian pesantren teachers’ perspectives - Madkur, Ahmad; As’ad, Muhammad Syihab (Makassar State University, 2024)
Abstract. In the dynamic landscape of language education, understanding the perspectives of educators within unique cultural and educational contexts becomes imperative for fostering effective learning environments. This qualitative study explores the perceptions and challenges faced by English language teachers in pesantren schools in Indonesia, where cultural, religious, and linguistic dimensions intricately influence language education. Through in-depth interviews, the research uncovers the complexities teachers navigate in balancing cultural preservation with the imperative of equipping students with English language skills. Findings highlight how English language teachers navigated the integration of ELT practices with students’ context and needs, primarily aiming to convey the importance of learning English, aligning it with Islamic teachings and dispelling misconceptions about its compatibility with religious principles. The study underscores the necessity for tailored pedagogical strategies and contributes insights to the discourse on language education in culturally rich settings.Keywords: English language teaching, teachers’ experiences, Indonesian pesantren